THE LANGUAGE CHOICE OF CHINESE COMMUNITY IN MEDAN: A SOCIOLINGUISTICS STUDY - Vivi Adryani Nasution; Niza Ayuningtyas (JOALL (Journal of Applied Linguistics and Literature), 2020)
This study aims to describe the manifestation of language choice and the dominant factors of determining language choice among Chinese community inter-ethnic and intra-ethnic relations in Medan. This study used descriptive qualitative method emphasized on a multiethnic and multilingual Chinese community background. The sociolinguistic theory of language choice focused on the domain features involving family and occupation domains was used as the basis of this study. It applied Miles and Huberman technique for analyzing the data and the Bungin formula for calculating the data. Of the 80 respondents, the results of the questionnaire showed that the Hokkien sub-ethnic was the dominant sub-ethnic in Medan compared to other Chinese sub-ethnicities. The manifestation of language choice in the domain of family and occupation especially in inter-ethnic relation is dominated by vernacular language, especially Hokkien language although respondents come from non-Hokkien ethnic. However,  Indonesia language becomes the main language used related to intra-ethnic relation. In addition, the dominant language choice factor is influenced by Chinese participant’s cultural backgrounds similarity.